Sistem Informasi Akademik Berbasis Web Pada SMA Yayasan Wanita Kereta Api Palembang - Muhammad Syahril; Pebriana. Pebriana (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
YWKA Palembang High School is one of the private high schools in the city of Palembang, which will certainly continue to grow in order to improve the competence and quality of its students. However, there are still some obstacles in the management of student data that still uses paper based as an archive. The purpose of this thesis is to build an academic information system at SMA YWKA Palembang to simplify and save time in the process of selecting teacher teaching schedules, final grades, searching for teacher and student data, and recap attendance. Where the design of this information system can be used as a medium to help make the information system more effective and efficient. The system is built using an iterative development methodology and uses the PHP and MySQL programming languages ​​as DBMS. The academic information system built can simplify all data management procedures to be more effective and efficient and become a medium for faster delivery of information.